Competitividad internacional mexicana en la Unión Europea: el caso del mango, 1996-2006 - Medina Chávez, Yenit (Universidad Michoacana de San Nicolás de Hidalgo, 2008)
Nowadays agriculture is one of the most important activities for thousands of Mexican homes. The fact that this sector may or may not be competitive is one of the biggest issues not only for economic growth but also for the development of the communities dedicated to this activity. The present thesis aims to identify the factors and levels of competitiveness in mango’s production and exports both in Mexico and at the international level, using the methodology used by SAGARPA. Proposed variables are six: productivity, producer’s return, profitability, position in domestic market, global and target market. Results on the measured variables suggest a low competitiveness throughout the study period (1996 - 2006), earning the lowest ratings in profitability and position of global market, and the highest in position in the domestic market. Based on results a number of conclusions and recommendations are given, these can be used to develop and implement strategies for growth in the competitiveness of Mexican mangoe in the international context.

La agricultura hoy en día constituye el pilar y sustento de muchos hogares mexicanos. El hecho de que este sector sea competitivo o no es decisivo para el desarrollo económico y social de las comunidades dedicadas a esta actividad. La presente tesis tiene como objetivo identificar los factores y niveles de competitividad de la producción y exportación del mango tanto en México como a nivel internacional, empleando la metodología usada por SAGARPA. Las mediciones de competitividad se basan en seis variables: productividad, retorno al productor, rentabilidad y posicionamiento en los mercados interno, global y meta. Los resultados en dicha medición sugieren niveles bajos de competitividad durante todo el periodo de estudio (1996 – 2006), obteniendo los niveles más bajos en rentabilidad y posicionamiento en el mercado global; mientras que los niveles más altos se encontraron en el posicionamiento del mercado interno. A partir de los resultados obtenidos surge una serie de conclusiones y recomendaciones, las cuales pueden servir para el desarrollo e implementación de estrategias que permitan un crecimiento de la competitividad del mango mexicano en el contexto internacional.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias en Comercio Exterior
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2008-0003; Agricultura; Mango; Competitividad; Mercado; Rentabilidad; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/916